Emergency decision-making model of suppliers with updating information in cases of sudden accidents. (December 2021) - Yang, Haidong; Chen, Luying; Liu, Biyu; Migdalas, Athanasios
Highlights: Suppliers' emergency procurement/production decision-making (EPD) is addressed. Supply disruption and retailer's procurement behaviour are considered. An information updating model is proposed base on Bayesian statistic method. A real-time updated EPD model under sudden accidents for suppliers is proposed. Information updating value and critical factors that affect the EPD are analysed. Abstract: In view of uncertainties caused by sudden accidents (SAs) and affecting retailers' demand in many districts, it is difficult for suppliers to determine when and how many products to procure/produce. Considering a supply chain consisting of two types of competing suppliers and multi-retailer, this work studies the suppliers' optimal emergency procurement/production decision (EPD) with information updating. Firstly, a probability evolution model with information updating to describe the probability of the retailers' procurement behaviour and the occurrence probability of supply disruption (SD) is inferred. Secondly, suppliers' EPDs regarding retailers' procurement behaviour and occurrence probability of SD are discussed and a real-time updated emergency decision-making model (EDM) is proposed based on Stackelberg game and Bayesian inference. Thirdly, the value of information updating and the critical factors that affect the suppliers' optimal EPD are quantitatively analysed. Numerical examples are finally provided to verify the EDM. Results indicate that information is the premise and foundation for the suppliers to deal with SA effectively; suppliers can easily determine when and how many products to procure/produce based on the proposed EDM; it is demonstrated that for any chosen supplier strategy, there exists a corresponding optimal procurement/production quantity for the suppliers that maximises the expected profits. Moreover, the suppliers' EPD with information updating is affected by cost parameters, with the rank of information collection cost coefficient, unit procurement/production cost, unit sales price, unit holding cost and unit shortage cost, from apparently to slightly.